A GdBCO bulk staggered array undulator. (11th December 2019) - Calvi, M; Ainslie, M D; Dennis, A; Durrell, J H; Hellmann, S; Kittel, C; Moseley, D A; Schmidt, T; Shi, Y; Zhang, K
Abstract: The Insertion Device group of the Paul Scherrer Institute has started an R&D program on a high temperature superconducting undulator to reduce the period length and increase the undulator's magnetic field well beyond the present capability. Simulation results for a 10 mm period and 4 mm magnetic gap staggered array of GdBCO bulks predict peak magnetic field above 2 T. Building on the existing working principle of undulator design and simulated performance, the first experimental results of a 5 period 6.0 mm gap short undulator measured in the new test facility available at the University of Cambridge will be presented together with details of the experimental setup and sample preparation.